A Spark of Humor in English Classroom: Contribution and Consideration - Pujiastuti, Ani (Journal of English and Education (JEE), 2009)
This paper supports an idea that humor has a significant role in increasing the English learners' communicative competence. It is very common for teachers to present humor in English classrooms, whether it is purposely presented or spontaneously practiced in classroom activities. Yet, regardless of its significant contribution in language learning activities, it is highly likely that humor is one point that remains untouched in language learning. How many English textbooks containing humor in it? We hardly ever find any syllabi purposefully present the ability of students to tell or to understand jokes. Telling jokes in a serious classroom maybe considered as something inappropriate as it may distract the classroom activities. Therefore, spontaneous humor may sometimes be viewed as an 'off task' behavior. However, it is sometimes forgotten that understanding other people's joke may be one of the keys of understanding other cultures, and ,more importantly, building a relationship with people from other countries.